SOCIO-ECONOMIC DIMENSIONS OF THE AL-IDRISIYAH TAREKAT IN INDONESIA: DOCTRINE AND PRACTICE - Mursalat Mursalat; Siswoyo Aris Munandar (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
Tarekat or Sufi order is identical to various spiritual activities, often considered far from worldly life. This identification places Sufism as merely related to mystical and ascetic activities. This study intends to explain how the Al-Idrisiyah tarekat in Indonesia has primary concern on social and economic dimensions in all of their various empowerment programs in the community. The research uses qualitative methods, with data collection techniques of observation and documentation of tarekat activities on mixed social media. The study results show that the practice of the socio-economic dimension is an implementation of their belief that a true Sufi is a Sufi who works and empowers others. Their socio-economic activities have developed to resemble philanthropic activities and can help several community groups affected by the pandemic in 2020-2021.Tarekat atau sufi sering diidentikkan dengan kegiatan spiritual, yang dianggap menjauhi kehidupan duniawi. Identifikasi tersebut menyebabkan tasawuf dianggap dekat dengan hal-hal yang bersifat kebatinan dan asketik. Penelitian ini bermaksud untuk menjelaskan bagaimana Tarekat Al-Idrisiyah di Indonesia memiliki dimensi sosial dan ekonomi yang diterapkan dalam berbagai program pemberdayaan mereka di masyarakat. Penelitian dilakukan dengan menggunakan metode kualitatif dengan teknik pengumpulan data berupa observasi dan dokumentasi kegiatan-kegiatan tarekat di berbagai sosial media. Hasil penelitian menunjukkan bahwa praktik dimensi sosial-ekonomi tersebut merupakan implementasi dari keyakinan mereka bahwa seorang sufi yang benar adalah sufi yang bekerja dan memberdayakan manusia lainnya yang lemah. Kegiatan sosial-ekonomi mereka tersebut berkembang menyerupaikan aktivitas filantropi dan mampu membantu beberapa kelompok masyarakat yang terdampak pandemi di tahun 2020-2021.